Primal, chemo and bacterial productivety coupled with inorganic nutrient concentrations from an off shore, out going transect cruises - Reich, Tom (PANGAEA, 2025)
Here, we report on both photic and aphotic primary productivity, dark carbon fixation and heterotrophic bacterial production rates from 6 cruises conducted in 2021-2023 at the offshore Southeastern Mediterranean Sea at stations covering the continental shelf (seafloor <200m), slope (200-1000m), and the offshore environments (maximum bottom ~1750 m) during the mixed (winter) and stratified (summer) periods. These cruises were conducted as part of the Israeli monitoring program. Samples where collected at discrete depths for carbon fixation productivity rates. Using a modified NaH14CO3 incorporation method (Nielsen 1952 10.1093/icesjms/18.2.117) we measured net, light (photosynthesis) and dark (chemosynthesis) productivity. Bacterial production was measured using the 3H-leucine incorporation method. Water samples were also collected for inorganic nutrient (Si(OH)4, PO4, NO2, NH4 and NO3) concentration measurements. These data were collected to better understand how much dark carbon fixation by chemoautotrophs contributes to net production in low nutrient, low chlorophyll areas. The data cover seasonal (summer, winter), spatial (continental, slope and open ocean) and vertical (photic and aphotic depths) to contrast the changes in these parameters for a better view of this dynamic system. All water samples were collected using Niskin bottles. Nutrient concentration were measured with a Seal Analytical AA-3 system, and productivety samples were measured with a TRI-CARB 4810 TR (Packard) liquid scintillation counter.
Keywords: chemoautotrophy; Dark carbon fixation; East Mediterranean Sea; Inorganic nutrients; primary productivity